The determinants of participation in global value chains: A cross-country, firm-level analysis - Shujiro Urata; Youngmin Baek (Asian Development Bank Institute (ADBI), 2020)
This paper attempts to identify the firm and country-related factors that determine a firm's probability of participating in global value chains (GVCs) and level of GVC participation by using data from the World Bank's Enterprise Surveys, covering 111 countries and 38,966 firms for the 2009-2018 period with a focus on small and medium-sized enterprises (SMEs). Our analysis shows that in terms of firm-related factors, high labor productivity, large firm size, foreign ownership, and high technological capability are important for a firm, and technological capability is particularly important for SMEs to enable them to participate in GVCs and to increase their level of engagement in GVC networks. As for country-related factors, openness to trade and foreign direct investment inflows, availability of educated people, well-developed infrastructure, efficient logistics, and good governance are found to facilitate firms' participation in GVCs and to increase the level of such participation. These attributes are particularly important for SMEs. Several policy recommendations and a future research agenda are discussed.
Keywords: F13; L11; 330; global value chains; small and medium-sized enterprises